Separation and the modified and interposition between the adjective noun- The Holy Qur’an as a model - Alagiri, Mohamed Taha Abd Alkhaleek; Wahdan, Amr Khater Abd Elghany; Hasanen, Mohamed Ibraheem; Ismail, Mohamed Eliwa Aly; Bouguerra, Naaman Abdulhamid; Ahmed, Mohamed Abdelnabi Mohamed; Sayed, Mohamed Abd Elrahman Mohamed; Ibraheem, Gomaa Elsayed Abd Elmaksoud (Research Journal in Advanced Humanities, 2026)
The Arabic language generally does not permit the separation of a follower* (Tabi’) from its antecedent (Matbu’) except in rare instances, often regarded as poetic necessity or linguistic anomalies that are memorized rather than used as a basis for analogy. Accordingly, this research aims to identify the interpolations separating the adjective (Sifa) and the modified noun (Mawsuf) within the Holy Qur’an. It provides a structural and semantic analysis of these separators while uncovering their functional dimensions and discussing related linguistic issues to determine what aligns with or contradicts the views of traditional grammarians. The research adopts a descriptive-analytical methodology. Among its key findings is the diversity of separators between the adjective and the modified noun in the Qur’anic text, including: (The delayed subject, the predicate, the agent/subject, the object, exception, conjunction, verbal clauses, apodosis of an oath, parenthetical sentences, explanatory sentences, phrasal structures, and conditional particles with their subsequent clauses). Furthermore, the study highlights novel instances not previously addressed by grammarians, such as the separation between an adjective and its noun located within a conditional response by the conditional particle and its clause, and separation via conjunctions and the coordinated noun. The semantic study also revealed significant rhetorical purposes, most notably: reinforcing and establishing facts in the listener's mind (as seen in separation by a delayed subject); glorification and suspense (evident in separation by parenthetical sentences); and capturing the listener's attention to emphasize the magnitude of an oath (as seen in separation by conditional structures). The researcher suggests further scientific studies on this separation within poems and prose texts to identify additional types of separators.